Prosesi Talak Menurut Hukum Islam: (Analisis Fiqh Al-Syafi’iyyah dan KHI) - Muhammad Basyir (Fakultas Syariah dan Ekonomi Islam, 2016)
Divorce is the legal deeds committed husband to sever the relationship of marriage. The implementation of the provisions of rule tied to divorce law in marriage, be it in the form of pillars as well as a requirement to be met in its implementation so that it allows a husband who feels the marriage bond can not be held its suﬆainability initiative so that the relationship with his wife. Writing this research describes the teﬆament of divorce, with the formulation of the problem is where the diﬀerence in the views of Fiqh Al-Syaﬁ’iyah and positive law of divorce teﬆimony. In order to describe the suitability of pelaksananan talak according to Fiqh Al-Syaﬁ’iyah and positive law. This research has the kind of qualitative approach, namely research not using numbers or ﬆatiﬆical research with formulation are deskriptive comperative, i.e. research which aims to give an overview about the facts, properties and compares the data with each other to see the similarities and diﬀerence in taking a conclusion. The technique used is the data collection technique “Library Research”. The results on positive law is applied today. So get realiﬆic results. Teﬆament of talak according to Fiqh Al-Syaﬁ’iyah explained in General, it is very diﬀerent to the positive law ﬆated that the teﬆament of divorce is an absolute requirement of which is regulated in the compilation of Islamic law in sections 115 and 117. In its application required the exiﬆence of a teﬆament of divorce, divorce, then declared invalid by court ruling Syar’iyah. In this case the author analyzes the development of positive law which applied in the practice of the Court of Syar’iyah the law of materilnya using a compilation of Islamic law, here seems to be to put forward the opinion of Shia imamiyah corresponding to pandapat (qawl qadim) Imam Al- Syãﬁ’i which requires the presence of two witnesses if someone would mentalak his wife.